HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN LANSIA DALAM PEMENUHAN AKTIVITAS SEHARI-HARI - Astika, Aulya Lintang Octa; Lestari, Puji (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p02, 2023)
The decrease in various organ functions in the elderly leads to a decrease in the independence of the elderly in the fulfillment of daily activities. It requires the support of the family. The phenomenon found, there are elderly people with good family supports but the fulfillment of daily activities is still low. This study was to determine the relationship between family support and the independence of the elderly in fulfilling daily activities. The design of this study is descriptive correlational with a cross sectional approach. 51 respondents were taken with purposive sampling technique. The measuring instrument used is a questionnaire Perceived Social Support-Family and  Lawton Instrumental Activity Everyday Living. The data obtained were analyzed using the chi square test. Most of family support is sufficient (60,8%) and the independence of the elderly in fulfilling daily activities is mostly independent (56,9%). There is a significant relationship between family support and the independence of the elderly in fulfilling daily activities with  p-value of 0,046 (< 0,05).